Place and Temporal Cues in Cochlear Implant Pitch and Melody Perception - Swanson, Brett A.; Marimuthu, Vijay M. R.; Mannell, Robert H. (Frontiers in Neuroscience, 2019)
The present study compared pitch and melody perception using cochlear place of excitation and temporal cues in six adult Nucleus cochlear implant (CI) recipients. The stimuli were synthesized tones presented through a loudspeaker, and recipients used the Advanced Combinational Encoder (ACE) sound coding strategy on their own sound processors. Three types of tones were used, denoted H3, H4, and P5. H3 tones were harmonic tones with fundamental frequencies in the range C3 to C4 (131 – 262 Hz), providing temporal pitch cues alone. H4 tones were harmonic tones with fundamental frequencies in the range C4 to C5 (262 – 523 Hz), providing a mixture of temporal and place cues. P5 tones were pure tones with fundamental frequencies in the range C5 to C6 (523 – 1046 Hz), providing place pitch cues alone. Four experimental procedures were used: pitch discrimination, pitch ranking, backward modified melodies, and warped modified melodies. In each trial of the modified melodies tests, subjects heard a familiar melody and a version with modified pitch (in randomized order), and had to select the unmodified melody. In all four procedures, many scores were much lower than would be expected for normal hearing listeners, implying that the strength of the perceived pitch was weak. Discrimination and ranking with H3 and P5 tones was poor for two-semitone intervals, but near perfect for intervals of five semitones and larger. H4 tones provided the lowest group mean scores in all four procedures, with some pitch reversals observed in pitch-ranking. Group mean scores for P5 tones (place cues alone) were at least as high as those for H3 tones (temporal cues alone). The relatively good scores on melody tasks with P5 tones were surprising, given the lack of temporal cues, raising the possibility of musical pitch using place cues alone. However, the alternative possibility that the CI recipients perceived the place cues as brightness, rather than musical pitch per se, cannot be excluded. These findings show that pitch perception models need to incorporate neural place representations alongside temporal cues if they are to predict pitch and melody perception in the absence of temporal cues.